A Case of Orbital Metastasis of Uterine Leiomyosarcoma With Intracranial Extension Presenting With Proptosis. Issue 3 (May 2016) - Kim, Yeon-Hee; Park, In-Ki; Min, Gyeong Eun; Jin, Kyung-Hyun; Shin, Jae-Ho
Abstract : A 57-year-old woman presented with protrusion of the OS 2 months in duration and decreased vision 1 month in duration. The patient was diagnosed with uterine leiomyosarcoma approximately 3 years before presentation. Lung and liver metastases were diagnosed by biopsy 1 year prior to this visit. CT revealed a solid mass with central necrosis in the left lateral orbit that resulted in orbital shifting, bony destruction, and intracranial extension. The diagnosis was left orbital metastatic leiomyosarcoma, and the patient died 2 months after receiving the diagnosis. Abstract : Leiomyosarcoma is rarely been encountered in the orbit and in addition, very few cases of metastatic orbital leiomyosarcoma have been reported in the medical literature. To our knowledge, only one case of orbital leiomyosarcoma with intracranial extension has been described previously. We herein report the case of a middle-aged female with metastatic orbital leiomyosarcoma showing intracranial extension.